Accuracy of D-Dimers to Rule Out Venous Thromboembolism Events across Age Categories - G. Der Sahakian; Y. E. Claessens; J. C. Allo; J. Kansao; G. Kierzek; J. L. Pourriat (Emergency Medicine International)
Background. Strategies combining pretest clinical assessment and D-dimers measurement efficiently and safely rule out venous thromboembolism events (VTE) in low- and intermediate-risk patients. Objectives. As process of ageing is associated with altered concentrations of coagulation markers including an increase in D-dimers levels, we investigated whether D-dimers could reliably rule out VTE across age categories. Method. We prospectively assessed the test performance in 1,004 patients visiting the emergency department during the 6-month period with low or intermediate risk of VTE who also received additional diagnostic procedures. Results. 67 patients had VTE with D-dimers levels above the threshold, and 3 patients displayed D-dimers levels below the threshold. We observed that specificity of D-dimers test decreased in an age-dependent manner. However, sensitivity and negative predictive value remained at very high level in each age category including older patients. Conclusion. We conclude that, even though D-dimers level could provide numerous false positive results in elderly patients, its high sensitivity could reliably help physicians to exclude the diagnosis of VTE in every low- and intermediate-risk patient.